IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA DI UPTD. PUSKESMAS LAWELE KECAMATAN LASALIMU - Ahmad Daholu; Suriadi Suriadi; Popi Popi (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2023)
This research aims to find out more about how human resource management is implemented through planning, procurement, development and compensation at the UPTD. Lawele Health Center Lasalimu District. This research use descriptive qualitative approach. Based on the exploration results, it shows that human asset management at the UPTD. Lawele health center, Lasalimu district said to be good, but still not optimal. There is preparation of plans for health programs, procurement of honorary staff to assist with equipment at the health center, development of education based on wishes and not planned by health workers, implementation of training planned by the health service, and compensation given in the form of salaries and appreciation awards for achievements, ease of reach and what is needed by health workers as well as compensation given based on class and profession. However, at the Lawele community health center there are multiple positions, this is because the Lawele community health center still lacks health workers or human resources, causing the workload to increase. Apart from that, the facilities and infrastucture of the Lawele community health center are inadequate, which affects patient service and comfort.